Les boutiques dans les colonies de Lyon et de Vienne entre le i er s. av. et le iii e s. apr. J.-C. - Marine Lépée (Frontière·s)
The shop (taberna), as a space dedicated to commercial transactions for sale, production and/or service activities, was a recurrent feature in the cities of Roman Gaul. It represented retail trade and local exchanges in urban areas. More than domestic space or public buildings, retail outlets tended to assert themselves as major interfaces in the urban fabric and therefore as places where the idea of a boundary became a reality and tended to be passed. So the purpose of this article focuses on the different forms that this expansion took and which archaeology can attest to : in what way did the commercial premises act as an interface? What associated structures allow us to refer to the encroachment of commercial activities or transgression within the urban space? Which traffic patterns were generated by these architectural and functional choices? The examples given here are taken from an ongoing thesis on urban retail trade in the Rhône Valley between the i st century BC and the end of the iii rd century AD conducted at the University of Lyon 2 and the University of Lausanne, under the supervision of M. Poux and T. Luginbühl. Parallels from other provinces of Roman Gaul and Italy will broaden the discussion.